PENGARUH BOKASHI LIMBAH PERTANIAN TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH PADA TANAH PMK - suryanto, suryanto (Jurnal Sains Pertanian Equator, 2019)
Onions is one of the vegetable commodities that has a high economic value and can be developed in low plains to the highland. The need for Onions in Indonesia is big enough, but these needs have not been met by producers. This study is meant to see the influence of the bokashi waste of agriculture and the best dose of growh and the yield of onions on the ground PMK. This research began on May 8 to July 4, 2018 on the land of the Faculty of Agriculture, University of Tanjungpura Pontianak. The method used is a completely randomized complete design (CRD) with 5 doses of treatment for agricultural waste (0 tons / ha, 10 tons / ha, 20 tons / ha, 30 tons / ha and 40 tons / ha) with 5 replications. Each test consists of 4 plant samples. Observation variables consisted of plant height, number of leaves, number of tillers, fresh weight of bulb, dry weight of bulb and number of bulb. Based on the results of the study, The use of bokashi`s of agricultural waste shows an increase in growth and results that are getting better. The treatment of bokashi doses of agricultural wastes of 40 tons / ha showed an increase in growth and improved yield on variable plant height 47.24 cm, number of leaves 23.95 strands, number of tillers 7.13 tillers. Fresh weight of tuber was 68.52 g, dry weight of tuber was 64.42 g and number of tubers was 8.65 tubers. The results of this study indicate an increase in growth and results are getting better than other treatments. Keywords : Spanish onion, compost agricultural waste, PMK.